Severe Pancreatitis After Renal Transplantation Due to Disseminated Cytomegalovirus Infection: A Case Report: Pancreatitis After Renal Transplantation - Hoseiny Nejad, Nasrin; Rahim Zadeh, Nahid; Eshghi, Alireza (Journal of Pediatric Nephrology, 2025)
Background and Aim: Cytomegalovirus (CMV) infection is considered one of the most common opportunistic infections and also a common cause of morbidity and mortality among patients receiving renal transplantation. Pancreatitis is a rare complication of CMV infection in renal transplant recipients, which can lead to death. Here, Case Presentation: we presented a 10-year-old boy who underwent a nonrelative living donor renal transplantation and was admitted due to early graft dysfunction two months after transplantation. Diagnostic tests for modalities showed CMV infection. The patient was treated with ganciclovir; however, he developed seizures and acute abdominal pain one week later. The brain MRI revealed increased signal intensity in the cortex and subcortex of the parieto-occipital lobe. Serum laboratory tests showed elevated levels of amylase and lipase. The patient was treated for CMV infection and pancreatitis. Conclusion: Finally, the patient died due to multi-organ failure caused by disseminated CMV infection two weeks after admission. These findings suggest that disseminated CMV infection and pancreatitis may occur after renal transplantation, with a high mortality rate.